THE DEVELOPMENT OF SCIENCE FICTION AS A LITERARY GENRE - Axmadjonova Nafosat Xayrullojon qizi The student of Chirchik State Pedagogical University Scientific adviser: Mavluda Abduvaliyevna Komiljonova Teacher, Chirchik State Pedagogical University (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Science fiction is known to have undergone substantial transformation from myth and speculative stories to the most precise and advanced kind of literature in the modern world. This study follows the transition in the history of literature in which SF became one of genres, giving particular attention to the genesis of SF in the nineteenth century, evolution of its themes, and growth in the twentieth and twenty first centuries. It addresses significant publications and writers who have been active in the development of this genre, such as Mary Shelley, H.G. Wells, Isaac Asimov, Ursula K. Le Guin and others. In addition, the article, touches upon the issues of how science fiction relates to technology, societal problems and culture issues and argues that SF is a category that describes and reacts to the society. This genre’s cross-cultural impact and its place in science are also highlighted.